Asteroid Shower: Cutaneous Silica Granuloma with Asteroid Bodies - Fadwa Ahmed; Christopher DiMarco (Dermatopathology)
Cutaneous silica granulomas are a form of foreign-body granulomatous reactions. They are characterized histopathologically by sarcoidal granulomas in association with silica crystals. Asteroid bodies, a classical histopathological feature of sarcoidosis, have not previously been reported in association with silica granulomas. Herein, we present the case of an 83-year-old man with an asymptomatic papule on the vertex scalp. Histopathology revealed a dermal granulomatous reaction to silica crystals. Asteroid bodies were observed in the cytoplasm of multinucleated giant cells. In the absence of systemic symptoms or laboratory findings suggestive of sarcoidosis, a final diagnosis of silica granuloma with asteroid bodies was made. While they have been observed in several other granulomatous reactions, the present case represents a novel association of asteroid bodies with silica granulomas.